2022
DOI: 10.1080/17430437.2022.2033220
|View full text |Cite
|
Sign up to set email alerts
|

The positive impact of sports participation on life skills’ development: a qualitative study with medical students

Abstract: We aimed to explore life skills development among medical student-athletes who participated in a university basketball team. We conducted qualitative constructivist research based on the life skills approach. Medical students from the college basketball team were interviewed in-depth. Using inductive thematic analysis, two independent researchers generated codes and themes. Methodological integrity and self-reflection process were carefully followed. Our analyses revealed that the medical students involved as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 68 publications
0
4
0
1
Order By: Relevance
“…The importance of sports for physical fitness and physical and mental well-being is well established. [ 2 3 ] Its role becomes even more important in the context of medical undergraduate course as most students are prone to sports-related injuries. In this context, it is pertinent to note that most students participate in sporting activities as evidenced by almost four-fifths of them responding in affirmative to the question of whether they play any sport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of sports for physical fitness and physical and mental well-being is well established. [ 2 3 ] Its role becomes even more important in the context of medical undergraduate course as most students are prone to sports-related injuries. In this context, it is pertinent to note that most students participate in sporting activities as evidenced by almost four-fifths of them responding in affirmative to the question of whether they play any sport.…”
Section: Discussionmentioning
confidence: 99%
“…Quinaud et al . [ 2 ] reported that medical students who were involved in college basketball were likely to perceive the associated life skill development to contribute to their future medical careers.…”
Section: Introductionmentioning
confidence: 99%
“…Em relação as características da amostra, foi possível identificar a relevância da interação entre diferentes ambientes sociais da sociedade civil que possuem o compromisso de contribuir com a formação de jovens, comprovando que além da estruturação esportiva a atuação da escola e da família pode potencializar o desenvolvimento de HV (Zhu et al, 2022) No Brasil foram incluídos os estudos de Ciampolini et al (2020) e Lunardelli et al (2020) realizados no ambiente educacional. Embora atualmente as investigações no esporte escolar sejam incipientes, no país é possível identificar a existência de artigos científicos efetuados no âmbito universitário (Quinaud et al, 2022), em modalidades esportivas individuais (Freire et al, 2020) e coletivas (Souza et al, 2020). Além disso, existem dissertações de mestrado (Nunes, 2019;Palheta, 2019) e teses de doutorado (Ciampolini, 2022;Mizoguchi, 2018) Além disso, alguns estudos adaptaram a escala de Cronin e Allen (2017), visando avaliar o ensino de HV pelo treinador (Camiré et al, 2019) e o desenvolvimento dessas habilidades na educação física escolar (Cronin et al, 2017;Cronin et al, 2020).…”
Section: Discussionunclassified

Família, escola e as HV no esporte: revisão sistemática

Bottega Lunardelli,
Fiorese,
Roberto Andrade do Nascimento Junior
et al. 2023
Estud. Interdiscip. Psicol.
Self Cite
“…For instance, athletes sharpen their decision-making skills by constantly evaluating the pros and cons of specific actions in game situations. The ability to make quick decisions becomes a guiding compass for individuals when making choices about their future [ 24 ], whether it is related to education, work, or relationships. Time management is a vital part of engaging in sports and serves as a crucial life skill.…”
Section: Literature Reviewmentioning
confidence: 99%